Global reporting of pulmonary embolism–related deaths in the World Health Organization mortality database: Vital registration data from 123 countries. Issue 5 (15th June 2021) - Barco, Stefano; Valerio, Luca; Gallo, Andrea; Turatti, Giacomo; Mahmoudpour, Seyed Hamidreza; Ageno, Walter; Castellucci, Lana A.; Cesarman‐Maus, Gabriela; Ddungu, Henry; De Paula, Erich Vinicius; Dumantepe, Mert; Goldhaber, Samuel Z.; et al.
Abstract: Introduction: Pulmonary embolism (PE) has not been accounted for as a cause of death contributing to cause‐specific mortality in global reports. Methods: We analyzed global PE‐related mortality by focusing on the latest year available for each member state in the World Health Organization (WHO) mortality database, which provides age‐sex–specific aggregated mortality data transmitted by national authorities for each underlying cause of death. PE‐related deaths were defined by International Classification of Diseases, Tenth Revision codes for acute PE or nonfatal manifestations of venous thromboembolism (VTE). The 2001 WHO standard population served for standardization. Results: We obtained data from 123 countries covering a total population of 2 602 561 422. Overall, 50 (40.6%) were European, 39 (31.7%) American, 13 (10.6%) Eastern Mediterranean, 13 (10.6%) Western Pacific, 3 (2.4%) Southeast Asian, and 2 (1.6%) African. Of 116 countries classifiable according to population income, 57 (49.1%) were high income, 42 (36.2%) upper‐middle income, 14 (12.1%) lower‐middle income, and 3 (2.6%) low income. A total of 18 726 382 deaths were recorded, of which 86 930 (0.46%) were attributed to PE. PE‐related mortality rate increased with age in most countries. The reporting of PE‐related deaths was heterogeneous, with an age‐standardized mortality rate ranging from 0 to 24 deaths per 100 000 population‐years. Income status only partially explained this heterogeneity. Conclusions: Reporting of PE‐related mortality in official national vital registration was characterized by extreme heterogeneity across countries. These findings mandate enhanced efforts toward systematic and uniform coverage of PE‐related mortality and provides a case for full recognition of PE and VTE as a primary cause of death.